Effect of polymer-coated silica particles in a Portland cement matrix via in-situ infrared spectroscopy. (February 2021) - Hafshejani, Tahereh Mohammadi; Feng, Chao; Wohlgemuth, Jonas; Krause, Felix; Bogner, Andreas; Dehn, Frank; Thissen, Peter
It is often of great importance in engineering to know precisely the properties of a material used with regard to its strength, its plasticity or its brittleness, its elasticity, and some other properties. For this purpose, material samples are tested in a tensile test by clamping the sample with a known starting cross-section in a tensile testing machine and loading it with a tensile force F. The force is then graphically displayed over the length change ΔL caused. This curve is called the force-extension diagram. In this study, a new measurement method enables for the first time, depending on the applied uniaxial stress, an insight at the atomic level into various energy dissipation processes at cement-based materials with the help of infrared spectroscopy. The samples are modified by adding SiO2 particles, which are coated by a polymer (PEG-MDI-DMPA) of different PEG molecular weights. Results show that elongating and breakage ofS i − O − S i andC − O bonds play an essential role in the strain energy dissipation. Compared to the pure cement, the modified samples are affected more by elongating and breakage ofS i − O − S i, as the admixture can effectively reduce the energy barrier of the hydrolytic reaction. The incorporating of particles into the cement matrix induces new mechanisms for energy dissipation by stretching ofO − S i − O bending vibrations. Stretching vibration of theO − H group indicates that part of the energy is dissipated by breakage of hydrogen bonding between the carboxyl group and PEG chains. Besides, a higher value of the ultimate fracture force following an increase in the molecular weight of PEG shows stronger bonding between particles and the cement matrix. As the chain-length of PEG is increased, less energy is absorbed through the other processes (especially at a higher level of strain). Thus, there is a balance between the whole deformation (toughness) and the strength of samples with the increase of the PEG molecular weight.